Burden of disease: A scoping review of HIV/AIDS and TB in occupational noise-induced hearing loss - Katijah Khoza-Shangase (South African Journal of Communication Disorders, 2020)
Background: Occupational noise-induced hearing loss (ONIHL) does not occur in isolation from other influencing factors such as health conditions and illnesses like human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS), as well as tuberculosis (TB). How the burden of disease influences the occurrence and/or management of ONIHL becomes a key if the goal of hearing conservation programmes (HCPs) is to be achieved within these contexts.